A preliminary study of the anti-inflammatory and anti-apoptotic effects of crocin against gastric ischemia-reperfusion injury in rats - Seyyed Ali Mard; Zahra Nikraftar; Yaghoob Farbood; Esrafil Mansouri (Universidade de São Paulo, 2015)
The aim of the present study was to investigate the protective effect of crocin on gastric mucosal lesions caused by ischemia-reperfusion (I/R) injury in rats. Thirty-two male rats were randomly divided into sham, I/R, I/R + crocin pretreatment and crocin alone groups. To induce I/R lesions, the celiac artery was clamped for 30 min, and the clamp was then removed to allow reperfusion for 3 h. Crocin-pretreated rats received crocin (15 mg/kg, i.p.) 30 min prior to the induction of I/R injury. Samples of gastric mucosa were collected to quantify the protein expression of caspase-3, an apoptotic factor, and inducible nitric oxide synthase (iNOS), a pro-inflammatory protein, by Western blot. Pretreatment with crocin decreased the total area of gastric lesions and decreased the protein expression levels of caspase-3 and iNOS induced by I/R injury. Our findings showed a protective effect of crocin in gastric mucosa against I/R injury. This effect of crocin was mainly mediated by reducing the protein expression of iNOS and caspase-3.